Single‐item discrimination of quality‐of‐life–altering dysphagia among 714 long‐term oropharyngeal cancer survivors: Comparison of patient‐reported outcome measures of swallowing. Issue 10 (11th January 2019) - ; Grant, Stephen; Kamal, Mona; Mohamed, Abdallah S. R.; Zaveri, Jhankruti; Barrow, Martha P.; Gunn, G. Brandon; Lai, Stephen Y.; Lewin, Jan S.; Rosenthal, David I.; Wang, Xin Shelley; Fuller, Clifton D.; et al.
Abstract : Background: Two patient‐reported outcomes (PROs) of swallowing and their correlation to quality of life (QOL) were compared in long‐term survivors of oropharyngeal cancer (OPC). Methods: Scores on the single dysphagia item from the 28‐item, multisymptom MD Anderson Symptom Inventory‐Head and Neck (MDA S I‐HN‐S) were compared with scores on the dysphagia‐specific composite MD Anderson Dysphagia Inventory (MDA D I) and the EuroQol visual analog scale (EQ‐VAS) in 714 patients who had received definitive radiotherapy ≥12 months before the survey. An MDA S I‐HN‐S score ≥6 and an MDA D I composite score <60 were considered representative of moderate/severe swallowing dysfunction. Results: Moderate/severe dysphagia was reported by 17% and 16% of respondents on the MDA S I‐HN‐S and the composite MDA D I, respectively. Both swallow PROs were predictive of QOL, and the MDA S I‐HN‐S model was slightly more parsimonious for the discrimination of EQ‐VAS scores compared with MDA D I scores (Bayesian information criteria, 6062 vs 6076, respectively). An MDA S I‐HN‐S cutoff score of ≥6 correlated best with a declining EQ‐VAS score ( P  < .0001) and was associated with increased radiotherapy dose to several normal swallowing structures. Conclusions: In this cohort, the single‐item MDA S I‐HN‐S performed favorably for the discrimination of QOL compared with the multi‐item MDA D I. A time‐efficient model for PRO measurement of swallowing is proposed in which the MDA D I may be reserved for patients who score ≥6 on the MDA S I‐HN‐S. Abstract : In a cohort of long‐term survivors of oropharyngeal cancer, a single dysphagia item from the MD Anderson Symptom Inventory‐Head and Neck Module (a 28‐item, multisymptom inventory) performs favorably in discriminating quality of life compared with the multi‐item MD Anderson Dysphagia Inventory (a 20‐item swallow quality‐of‐life measure). A model of patient‐reported outcome measurement of swallowing is proposed in which the MD Anderson Dysphagia Inventory may be reserved for those reporting moderate‐to‐severe symptoms by a single dysphagia item from the MD Anderson Symptom Inventory‐Head and Neck Module.